QUALITY RESEARCH IN AUDITS - Gabriele, Hahne (European Scientific Journal, ESJ, 2014)
During the financial crisis multiple company scandals led to high financial damage for shareholder. This led to an international discussion over the quality of audits, since prior to this almost all of the affected companies concerned had received an unrestricted audit certificate. To regain the trust in statutory audits, political leaders were forced to take action, the European Union passed the Directive 2006/43/EC.2 This article contains an analysis of how different researchers on the topic, such as Linda Elizabeth DeAngelo, Kai-Uwe Marten, Matthias Rebhahn and Mark Leuchtmann, describe and evaluate quality in audits. These researchers focused either on direct or indirect audit quality research, which will be outlined after a short description of the different definitions. Afterwards, a short abstract of a research project conducted by the author will be presented. Here it is outlined if the size of an auditing company has an effect on the quality of audits.